Economic and technical aspects of plug-in electric vehicles in electricity markets - Shafie Khah,M (2016)
In this paper, the management of PEVs, uncontrolled or controlled (i.e. aggregated), and their ability to use V2G and G2V technologies are first analysed. The electricity markets are then considered; real world applications are discussed and different market types categorised. The interaction of the PEVs with some renewable energy sources (e.g. solar, wind and biomass) is also examined, and the interaction of the PEVs with demand response programs addressed. Finally, the models of PEVs are categorised and multiple types of modules, the related variables, applied methods and the considered parameters are presented.